Ventral mandibulectomy for removal of oral tumours in the dog: Surgical technique and results in 19 cases. (1st July 2019) - de Mello Souza, Carlos H.; Bacon, Nicholas; Boston, Sarah; Randall, Victoria; Wavreille, Vincent; Skinner, Owen
Abstract : The purpose of this retrospective study is to describe in detail a novel ventral approach for mandibulectomy and the results in 19 dogs. The medical records of 19 dogs that received a partial or total unilateral mandibulectomy with the new ventral approach were reviewed. Information obtained included signalment, tumour type, extent of mandibulectomy, removal of regional lymph nodes, intrasurgical complications, immediate postoperative complications, histopathological diagnosis and study of margins. Intrasurgical complication occurred in one dog (haemorrhage) and required a blood transfusion. Postoperative morbidity was minor and included transient ventral cervical swelling and self‐limiting sublingual swelling (two dogs). All 19 animals were discharged between 24 and 48 hours of the procedure, and appetite was considered normal at discharge. Some perceived advantages of this procedure include easy identification of all the important anatomic structures in the area, including the inferior alveolar artery and temporo‐mandibular joint, and the fact that osteotomy of the zygomatic arch is not necessary (in case of caudal mandibulectomy). In addition, dissection of both mandibular and retropharyngeal lymph nodes is easily achieved by caudal extension of the same skin incision.